Rebranding Strategies for Educational Institutions: A Case Study of SMP Muhammadiyah 2 Kartasura - Dzikrillah, Jordan Amran; Ariansyah, Mochamad Yunus; Hanin, Jihan Al; Rosyadah, Sirly Amria; Fairuz , Sayida Abqaria; Purnomo, Purnomo (LPPM Institut Pendidikan Nusantara Global, 2025)
SMP Muhammadiyah 2 Kartasura is one of the schools that successfully increased student enrollment by 300% in the past year after appointing a new principal. This significant transformation was driven by the new principal's rebranding efforts, which introduced various modern initiatives across multiple aspects of the school to create a more distinct, appealing, and competitive image. This research employs a qualitative approach with a case study method, gathering data through interviews, observations, and documentation to analyze the impact of these strategic changes. This study SMP Muhduta, the rebranding strategies M implemented to increase student enrollment and enhance the school's image, making it more positive, attractive, and high-quality. The findings show that the school achieved notable success in rebranding initiatives critical, including scholarship programs for orphans and underprivileged students, providing each student with a laptop to support digital learning, organizing monthly outing classes to promote experiential education, a “one-student-one-medal” program to encourage individual achievement, and the distribution of 1,000 proposals to generate interest, community involvement, and funding support. These efforts collectively contributed to a revitalized school image. They strengthened public interest, illustrating the critical role of strategic rebranding in boosting school appeal, building trust, and encouraging broader community participation in education.